Avrupa'da İşgal Hareketlerinin Kapsamı ve Türkiye Örneği: Don Kişot Sosyal Merkezi - (:unkn) unknown (My University, 2016)
Çalışmanın amacı, Don Kişot Sosyal Merkezi örneği üzerinden küresel anlamda dönüşüm geçiren yeni toplumsal hareketlerden squatters/işgal evi hareketinin Türkiye'ye özgü özelliklerini ortaya koyabilmektir. Çalışma post-modern çağda dönüşüm yaşayan toplumsal hareketlerin yeni halini, söz konusu hareketlerde yer alan aktörlerin söylemleri ve eylemleri üzerinden anlamayı hedeflemektedir. Bu bağlamda, Türkiye örneği üzerinden hareket ederek, Gezi Parkı protestoları sonrasında daha görünür hale gelen ve dünyadaki "Occupy (İşgal Et )" hareketinin de bir uzantısı olabileceğini varsaydığımız İstanbul'un Kadıköy semtinde yer alan Yeldeğirmeni mahallesindeki Don Kişot Sosyal Merkezi sakinlerinin yaşam tarzları, mahalle bazında uygulamaya geçirdikleri yerel siyaset anlayışları ve küresel squatters/işgal evi hareketi ile kurduğu ilişki incelenmektedir. işgal edilmektedir? Bu sorudan hareketle, kentsel-kamusal mekânların yerel düzeyde işgal edilmesi ve yerleşilmesi hareketinin kültürel, siyasal ve küresel etkileri sorunsallaştırılmaktadır.Bu bağlamda, çalışma saha araştırmasına dayanmaktadır. Yarı yapılandırılmış mülakat ve gözlem, çalışma kapsamında kullanılan yöntemlerdir. Saha araştırmasından elde edilen veriler, yeni toplumsal hareketler kuramları ile sentezlenmiştir. Çalışma, Avrupa'da ortaya çıkan Yeni Toplumsal Hareketler Kuramı'ndan faydalanmaktadır.

The aim of the study is to reveal the features special to Turkey of squat as a new social movements transformed globally. The study intends to understand new form of the social movements transformed in the post-modern age, by examining the discourses and the actions of the actors who take part in these movements. In this context, Don Quixote Squat's habitants' life style, sense of local politics and relations with the global squatters movement are analysed. It supposes that Don Quixote Squat, which locates which is located in Yeldegirmeni, Kadıköy and has became visible following the Gezi Parki protests, might be an extension of the global Occupy Movement. The effects of the Occupy Movements of squares, streets or public spheres against the current governments, started in 2010 and spread out the world by internet networks, have still continued. This social movement also came up in the context of Gezi Parki Protests in Turkey. With the arrival of winter, the squatters who were organizing forums in the squares and parks needed enclosed spaces. Due to this requirement, Don Quixote Squat appeared in Yeldegirmeni as a first squat of Turkey.This study, working out the motivation that gets closer the group of differences and pushes them to act together, emphasizes how the (individual) action based on reconstruction of public spheres where the differences encounter and intersect can create collective action.The actors of this new social movement, who are opening alternative ways against present political, social and economic institutions and creating a new political, social and economic order, aim to built new alternative social spaces to where they feel belong. In this study, this new process is examined. The study tries to find an answer for the questions of how the squatters movement as a new social movement practiced in Turkey is influenced by the global squatters movement and other new social movements and political perception. Why public squares, parks, streets and the buildings (object of the research) are occupied? On the basis of these questions, the cultural, political and global effects of locally occupying and squating movement of the urban-public spaces is problematized.In this context, the study bases on the field research. Semi-constructed interviews and observations are the methods which were used for the field research. The data obtained from the field research was synthesized with the new social movements theory. The study benefits from the New Social Movements Theory emerging in Europe.
The Scope of the occupy Movements in Europe and the Case of Turkey: Don Quixote Squat
Keywords: Uluslararası İlişkiler; Siyasi Bilimler; Sosyal Çalışma; Sosyoloji